Our Families - Marta Delgado Pinto (Journal of Science and Technology of the Arts, 2023)
Yasujirô Ozu’s Tōkyō Monogatari (1953) is often considered as one of the best movies ever made. Within Portuguese cinema, it inspired João Botelho to make his 1986 piece Um Adeus Português. This audio-visual essay attempts to explore the films’ similarities and expose the hearts of both their stories, which are, at their core, simple and moving depictions of families.